2018
DOI: 10.1093/mspecies/sey002
|View full text |Cite
|
Sign up to set email alerts
|

Canis aureus (Carnivore: Canidae)

Abstract: Canis aureus (Linnaeus, 1758), the golden jackal, is a medium-sized, wide spread, terrestrial carnivore. It is 1 of 7 species found in the genus Canis. It ranges from Africa to Europe, the Middle East, Central Asia, and Southeast Asia. Due to its tolerance of dry habitats and its omnivorous diet, C. aureus can live in a wide variety of habitats. It normally lives in open grassland habitat but also occurs in deserts, woodlands, mangroves, and agricultural and rural habitats in India and Bangladesh. It ranges fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 65 publications
1
29
0
7
Order By: Relevance
“…It is clear, however, that there is no reason to consider these morphological differences as evidence for the existence of more than one subspecies on the Balkans and adjacent European countries. The subspecies Canis aureus ecsedensis (Kretzoi, 1947), or its synonym Canis aureus hungaricus Ehik, 1938 (Moehlman andHayssen 2018), could not be justified as a separate subspecies in Europe, based on the present morphometric results. Genetic studies so far revealed that jackals in Europe are genetically similar, despite high level of genetic diversity and higher genetic differentiation in some European populations (Zachos et al 2009;Fabbri et al 2014;Rutkowski et al 2015).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…It is clear, however, that there is no reason to consider these morphological differences as evidence for the existence of more than one subspecies on the Balkans and adjacent European countries. The subspecies Canis aureus ecsedensis (Kretzoi, 1947), or its synonym Canis aureus hungaricus Ehik, 1938 (Moehlman andHayssen 2018), could not be justified as a separate subspecies in Europe, based on the present morphometric results. Genetic studies so far revealed that jackals in Europe are genetically similar, despite high level of genetic diversity and higher genetic differentiation in some European populations (Zachos et al 2009;Fabbri et al 2014;Rutkowski et al 2015).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, there is no significant difference in the colouration pattern and other features across the various subpopulations living in this area (Pocock 1938;Heptner et al 1967;Demeter and Spassov 1993). Although the subspecies Canis aureus caucasica Kolenati, 1858 was proposed as synonym of Canis aureus aureus Linnaeus, 1758 (Moehlman and Hayssen 2018), there is no evidence that the Caucasian jackals belong to this subspecies. Morphometric similarities found in the present study and the ongoing genetic flow between the Caucasus and Europe (Rutkowski et al 2015) raises the question of the geographic border between Canis aureus moreotica and Canis aureus aureus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations